PENGARUH ASSET STRUCTURE, SALES GROWTH DAN COMPANY GROWTH TERHADAP DEBT POLICY - Carolina, Imelda; Bangun, Nurainun (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to determine the effect of asset structure, sales growth and company on debt policy in manufacturing companies listed on Indonesia Stock Exchange (IDX) for the 2017-2020 period. This research used 51 manufacturing companies as sample that were selected using purposive sampling method. Data was processed by Eviews 12 program. The result of this research show that asset structure has a negative significant effect on debt policy,sales growth has a positive significant and company growth has a positive not significant effect on debt policy. hypothesis testing is carried out using a panel data regression model.